Bridging Informal Learning and Sustainable Development: The Mediating Role of Entrepreneurial Mindset in Shaping SDG-Oriented Entrepreneurial Intention - Nurhayani, Nurhayani; Haruna, Hasisa; Kemalasari, Andi Anggi; Akbar, Muhammad (Indonesian Journal of Business and Entrepreneurship Research, 2026)
This study examines the role of informal entrepreneurship education in shaping SDG-oriented entrepreneurial intention, with entrepreneurial mindset as a mediating variable among students of the Department of Economics and Development Studies, Faculty of Economics, Universitas Tadulako. Using a quantitative approach, data were collected from 90 respondents and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that informal entrepreneurship education does not have a significant direct effect on SDG-oriented entrepreneurial intention. However, it has a positive and significant effect on entrepreneurial mindset, which in turn significantly influences SDG-oriented entrepreneurial intention. Furthermore, the findings reveal that entrepreneurial mindset fully mediates the relationship between informal entrepreneurship education and SDG-oriented entrepreneurial intention. These results highlight that informal learning alone is insufficient to foster sustainable entrepreneurial intention unless it is transformed into a strong entrepreneurial mindset. This study contributes to the literature by emphasizing the critical role of entrepreneurial mindset as a key mechanism linking informal learning and sustainability-oriented entrepreneurial intention. The findings also provide practical implications for educators and policymakers in designing entrepreneurship programs that support the achievement of the Sustainable Development Goals (SDGs).